Adaptive Sensing Private Property Protection Protocol Based on Cloud. (25th November 2015) - Fan, Kai; Wang, Wei; Li, Hui; Yang, Yintang
Abstract : Private property refers to something carrying private information, or expensive items; these items are very important for companies or individuals. The proposed private property protection system uses adaptive sensing technology to protect private materials in real time. In this paper, we propose an adaptive sensing private property authentication scheme which can be applied in the cloud computing. Considering a relatively safe room with a remote reader, there are several valuable items in the room. Each item is labeled with a unique tamper-evident adaptive sensor and the reader can simultaneously read a plurality of sensors. Encrypted information of items, sensors, and readers is stored in the cloud. The reader reads sensors and uploads the collected data to the cloud for further processing in real time. The proposed scheme is under the cloud environment to protect the user privacy and prevent synchronized attacks. Compared with some traditional schemes, our scheme is economical, practical, and easy to be expanded. Furthermore, it pays attention to privacy protection with real-time monitoring.